DEVELOPMENT OF AUGMENTED REALITY MEDIA FOR AUTOMATION OF MANAGEMENT OF OFFICE FACILITIES AND INFRASTRUCTURE IN VOCATIONAL HIGH SCHOOLS - Putri, Lavia Meiras; Faslah, Roni; Marsofiyati (Faculty of Economics and Business, Universitas Negeri Jakarta, 2025)
This study aims to develop Augmented Reality (AR)-based learning media called